(-f-9)+(9x+2)=

Simple and best practice solution for (-f-9)+(9x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-f-9)+(9x+2)= equation:


Simplifying
(-1f + -9) + (9x + 2) = 0

Reorder the terms:
(-9 + -1f) + (9x + 2) = 0

Remove parenthesis around (-9 + -1f)
-9 + -1f + (9x + 2) = 0

Reorder the terms:
-9 + -1f + (2 + 9x) = 0

Remove parenthesis around (2 + 9x)
-9 + -1f + 2 + 9x = 0

Reorder the terms:
-9 + 2 + -1f + 9x = 0

Combine like terms: -9 + 2 = -7
-7 + -1f + 9x = 0

Solving
-7 + -1f + 9x = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + -1f + 7 + 9x = 0 + 7

Reorder the terms:
-7 + 7 + -1f + 9x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + -1f + 9x = 0 + 7
-1f + 9x = 0 + 7

Combine like terms: 0 + 7 = 7
-1f + 9x = 7

Add '-9x' to each side of the equation.
-1f + 9x + -9x = 7 + -9x

Combine like terms: 9x + -9x = 0
-1f + 0 = 7 + -9x
-1f = 7 + -9x

Divide each side by '-1'.
f = -7 + 9x

Simplifying
f = -7 + 9x

See similar equations:

| -0.1+8.56=-0.3x+2.36 | | -3t^2+18t-4=0 | | -7y-7=-6y-8 | | 11x-9=6x+36 | | 8/2y-10=-2 | | 3t^2+18t-4=0 | | 1073/2941=56.7/x | | 36=x-12 | | 3(x+2)+5(2x+1)=27 | | -x+6=-27 | | -10=17+x | | 3lox=3.3 | | 177=-y+65 | | -2x+5=-1x+1 | | 3logx=3.3 | | -1x+1=-12 | | 9/x=63/77 | | 5u+3=33 | | 19x+5y=7 | | 17p^2+16=2151 | | f(x)=x^3-1.5x^2-1 | | N/400=2/100 | | 13p^3-3=4209 | | x^(5/3)=1.10 | | 9(11-k)=3(3k-6) | | 4x^2-x+29=0 | | 4x-2=-4-12x | | 4x-2=-4-12 | | 16pqr^2/2pq^2r | | 6(x-2)/5-3(x+1)/5=2(x-5) | | -3cos(2x)-7cos(X)-5=-7 | | 27x^2-25=0 |

Equations solver categories